DETECTION OF PULMONARY TUBERCULOSIS—Comparative Value of Routine Radiologic Examinations and Routine Laboratory Procedures - Peabody, Homer D. (1950)
The abnormalities disclosed by the usual laboratory diagnostic procedures (blood cell count and hemoglobin determination, sedimentation rate determination, urinalysis, and serologic test for syphilis) are compared with the number revealed by stereophotoroentgen chest examination in a series of 951 patients. The number of significant abnormalities uncovered by the routine stereophotoroentgen examination of the chest was comparable to the number disclosed by the usual laboratory procedures used in patient evaluation. Some form of radiologic examination of the chest should be included in the routine laboratory procedures required for patient evaluation.